Answer: x = -53/54 & y = -16/9 Step-by-step explanation: Given: 12x – 10y – 6 = 0 or, 12x – 10y = 6 …(i) 18x = 6y – 7 or, 18x – 6y = -7 …(ii) Solution: On multiplying 3 into (i) and 2 into (ii) 36x – 30y = 18 ….(iii) 36x – 12y = -14 ….(iv) On substracting (iii) from (iv) (36x – 12y) – (36x – 30y) = -14-18 => 36x – 36x +30y – 12y = -32 => 18y = -32 y = -32/18 = -16/9 On putting y = -16/9 in (i) 12x – 10*(-16/9) = 6 => 12x + 160/9 = 6 => 12x = 6 – 160/9 => 12x = (54 – 160)/9 => 12x = -106/9 => x = -106/(9*12) x = -53/54 Therefore, x = -53/54 & y = -16/9. ANS. Reply

Answer:## x = -53/54 & y = -16/9

Step-by-step explanation:Given:## 12x – 10y – 6 = 0 or, 12x – 10y = 6 …(i)

## 18x = 6y – 7 or, 18x – 6y = -7 …(ii)

Solution:On multiplying 3 into (i) and 2 into (ii)## 36x – 30y = 18 ….(iii)

## 36x – 12y = -14 ….(iv)

On substracting (iii) from (iv)## (36x – 12y) – (36x – 30y) = -14-18

## => 36x – 36x +30y – 12y = -32

## => 18y = -32

## y = -32/18 = -16/9

On putting y = -16/9 in (i)## 12x – 10*(-16/9) = 6

## => 12x + 160/9 = 6

## => 12x = 6 – 160/9

## => 12x = (54 – 160)/9

## => 12x = -106/9

## => x = -106/(9*12)

## x = -53/54

Therefore, x = -53/54 & y = -16/9.ANS.